Bodies tell stories: Freudian hysteria in Fay Weldon's The Life and Loves of a She-Devil - Abdullah, Omar Mohammed; Abdullah, Mustafa Mohammed (Universiti Putra Malaysia Press, 2017)
Fay Weldon's The Life and Loves of a She-Devil deals with the nature of the hysteric psychological state women in abusive relationships or situations may suffer from and how they may react in either passively relenting to these conditions or taking control of their lives to achieve change. Thus, the question is raised as to whether the hysteric condition may be used as a means to an end. Women's Freudian hysterical symptoms are often physically manifested by anorexia nervosa, loss of speech (muteness), disturbed sleep, and alienation, among other maladies which may be subsumed under the category of symptoms of Freudian hysteria. Such symptoms, according to Freud, appear as the consequences of sexual violations a subject may have encountered, resulting in the manifestation of psychological disturbances characteristic of hysteria. This paper aims to investigate Fay Weldon's The Life and Loves of a She-Devil from Freud's theoretical perspectives on hysteria in order to indicate the influences of hysteria and its symptoms and reactions, focusing on the actions taken by the heroine of the novel under discussion to actualise herself.